2012
DOI: 10.1128/aac.05966-11
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Proteus mirabilis Bloodstream Infections: Risk Factors and Outcomes

Abstract: Our aims were to identify (i) risk factors associated with the acquisition of multidrug-resistant (MDR, to 3 or more classes of antimicrobials) Proteus mirabilis isolates responsible for bloodstream infections (BSIs) and (ii) the impact on mortality of such infections. Risk factors for acquiring MDR P. mirabilis BSIs were investigated in a case-case-control study; those associated with mortality were assessed by comparing survivors and nonsurvivors in a cohort study. The population consisted of 99 adult inpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 46 publications
6
55
2
2
Order By: Relevance
“…High antimicrobial resistance has also been observed in many studies. [12161718192021] Resistance to carbapenems in the present study was 12.5% which is in accordance with the studies of Datta et al . [21] and Bahashwan and Shafey;[14] however, other studies have reported a very low resistance of 0%–1%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…High antimicrobial resistance has also been observed in many studies. [12161718192021] Resistance to carbapenems in the present study was 12.5% which is in accordance with the studies of Datta et al . [21] and Bahashwan and Shafey;[14] however, other studies have reported a very low resistance of 0%–1%.…”
Section: Discussionsupporting
confidence: 92%
“…All P. penneri isolates were isolated from pus specimens which is similar to other studies[1119] whereas Kamga et al . in their study isolated 3%, all of which were from urine specimens.…”
Section: Discussionsupporting
confidence: 86%
“…In humans, ESBL-producing enterobacteria are closely associated with nosocomial infections (GIGUÈRE et al, 2010). High hospital mortality was reported in 99 patients with septicemia resulting from multiple drug-resistant P. mirabilis infection; 50% of these patients were infected with ESBL-positive strains, and 30 of these individuals died from these infections (TUMBARELLO et al, 2012).…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…P. mirabilis is a commensal enteric bacterium involved in community and health-acquired infections that can harbour many different mechanisms of antibiotic resistance. 16 To date there are five reports of SGI1-producing P. mirabilis concerning a patient from Palestine, humans and food in China and two French patients. 6,7,17 -19 In all but one case the genes contained in the MDR region are similar to those encountered in Salmonella from different serovars.…”
Section: Introductionmentioning
confidence: 99%